Caminhos para o investimento privado nas economias emergentes: As características institucionais e os spreads corporativos - Katia Rocha; Ajax Moreira; Gabriel Fiuza; Marcelo Pessoa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The study analyses the role of institutional characteristics of a country (governance) and the domestic financial system (depth, efficiency, stability, and capital openness) in determinants of emerging market corporate bond spreads issued in international market. We propose an econometric panel data with corporate bond spreads of CEMBI Broad Diversified Index in the period of 2002-2011 to twenty emerging economies. The sovereigns analyzed: Argentina, Brazil, Chile, China, Colombia, India, Indonesia, Kazakhstan, South Korea, Malaysia, Mexico, Peru, Philippines, Russia, Singapore, South Africa, Thailand, Turkey, Ukraine and Venezuela corresponded to roughly 80% of CEMBI Broad Diversified Index in July 2013. We conclude that policies that promote financial liberalization, capital openness, fiscal austerity, development of domestic financial system and improve governance institutional characteristics as rule of law and regulatory quality have the potential to reduce emerging market corporate bond spreads, especially in moments of global risk aversion. Results indicate that initiatives looking forward the improvement of institutional government apparatus and capital market development may help emerging market companies to increase the share of private capital investment.
Keywords: G15; G18; G38; 330; corporations; emerging markets; CEMBI; institutional characteristics; private investments